Transient Stability Analysis of Grid-connected Wind Turbines with Front-end Speed Control via Information Entropy Energy Function Method - Haiying Dong; Shuaibing Li; Shubao Li; Hongwei Li (Institute of Advanced Engineering and Science, 2014)
According to the characteristics like time-consuming and can not be quantitatively analyzed of time domain simulation in power system transient stability analysis, a direct method using information entropy combined with transient energy function method is proposed in this paper to analyze the transient stability of wind power system equiped with front-end speed controlled wind turbines (FSCWT) with synchronous generators. In which, the system kinetic energy and potential energy are used as information source to makeup information entropy function, then, a theoretical analysis of system transient stability is conducted. Based on this, simulations are carried out in IEEE 5-machine 14-bus system compared with the time domain’s, which verified the consistency of information entropy energy function (IEEF) method and time domain analysis. Results show that it is more intuitively and effectively to use IEEF method for wind power system transient analysis equiped with FSCWT.DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3379